SAT0231 MULTIDIRECTIONAL DYSFUNCTION OF THE IMMUNE RESPONSE IN SYSTEMIC LUPUS ERYTHEMATOSUS. (2nd June 2020) - Ramirez, G. A.; Sorce, A.; Mazzi, B. A.; Moroni, L.; Della Torre, E.; Colombo, G.; Yacoub, M. R.; Bozzolo, E.; Dagna, L.; Manfredi, A.
Abstract : Background: Systemic lupus erythematosus (SLE) is a multi-organ immune-mediated disease characterised by autoimmunity. Dysfunction in immune tolerance towards allergens and protection from infections has less been studied. Human leukocyte antigen (HLA) genotype affects the risk of developing SLE. Little is known on the role of HLA in shaping SLE phenotype. Objectives: To test for potential associations among active SLE, occurrence of infections and hypersensitivity reactions (HyR) at a clinical level and assess whether these events segregate with patients' HLA-DRB1 typing. Methods: 224 patients with SLE were prospectively followed up over the course of 1267 consecutive visits with a median interval of five months between each visit. HyR occurring within one month before or after each visit and occurrence of at least one infection leading to antimicrobial treatment and/or absence from work in the interval between each visit were recorded. Disease activity was estimated through the systemic lupus erythematosus disease activity index 2000 (SLEDAI-2K). Remission was surrogated by the Lupus Low Disease Activity State (LLDAS). Demographics and general disease features including a previous history of allergy were retrospectively assessed. HLA-DRB1 genotype was obtained from 188 patients. Data are expressed as median [interquartile range], unless otherwise specified. Results: Incidence rates for HyR and infections were 80/1000 person-years and 45/100 person-years. Culprit agents for HyR were drugs in 61% of cases, inhalants, food or other allergens in the remainder 42%. Most frequent sites for infections were the airways (55%), skin and mucosae (16%), the genital and/or urinary tracts (14%) and the gastrointestinal tract (7%). LLDAS was inversely associated with HyR (χ 2 =20.912; p<0.0001) or infections (χ 2 =8.234; p=0.005). patients with a recent HyR had a shorter disease duration (9 [2-15] vs 13 [8-22] years; p=0.006) and higher SLEDAI-2K scores (4 [3.5-11] vs 3 [2-4]; p<0.001) compared to patients without recent HyR. HyR were more frequently observed close to recent infections (χ 2 =15.509; p<0.0001). Patients with HLA-DRB1*11:01 (n=28/188) had more frequently a history of allergy than patients with other HLA-DRB1 genotypes (χ 2 =4.944; p=0.035). Among patients with at least four prospective visits, HLA-DRB1*11:01 carriers reported a recent infection more frequently (25% [13-40%] vs 14% [0-29%]; p=0.044) and HLA-DRB1*07:01 carriers less frequently (0% [0-17%] vs 18% [11-33%]; p=0.026) compared to patients with other HLA-DRB1 genotypes. Conclusion: These data suggest that immune dysfunction in SLE not only affects tolerance to self antigens but also antimicrobial and allergic responses and that genetically determined HLA-restricted mechanisms of antigen presentation might influence the shape of this dysfunctional immune response in patients with SLE. References: [1]Teruel M et al. Curr Opin Rheumatol, 2016 [2]Sequeira JF et al., Lupus, 1993 [3]Danza A et al, Lupus, 2013 [4]Park H et al., Allergy Asthma Immunol Res, 2012 [5]Quiralte J et al., J Allergy Clin Immunol, 1999 Disclosure of Interests: Giuseppe Alvise Ramirez: None declared, Andrea Sorce: None declared, Benedetta Allegra Mazzi: None declared, Luca Moroni: None declared, Emanuel Della Torre: None declared, Giselda Colombo: None declared, Mona-Rita Yacoub: None declared, Enrica Bozzolo: None declared, Lorenzo Dagna Grant/research support from: The Unit of Immunology, Rheumatology, Allergy and Rare Diseases (UnIRAR) received unresctricted research/educational grants from Abbvie, Bristol-Myers Squibb, Celgene, Janssen, Merk Sharp & Dohme, Mundipharma Pharmaceuticals, Novartis, Pfizer, Roche, Sanofi-Genzyme, and SOBI., Consultant of: Prof Lorenzo Dagna received consultation honoraria from Abbvie, Amgen, Biogen, Bristol-Myers Squibb, Celltrion, Novartis, Pfizer, Roche, Sanofi-Genzyme, and SOBI., Angelo Manfredi: None declared